2017
DOI: 10.1097/mph.0000000000000902
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Feeding Tubes in Pediatric and Adolescent Cancer Patients: A Single-institution Retrospective Review

Abstract: The purpose of our study was to evaluate surgical enteric access in pediatric cancer patients to determine factors associated with postoperative complications. We performed a single institution retrospective review of all patients<21 years old with a primary cancer diagnosis who underwent surgical procedures for enteral access between 2004–2014. Multivariate logistic regression was performed to determine independent predictors of postoperative complications. During the study period, 122 patients had surgically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…One study was translated from French 36 ; others were in English. All but two studies 17,36 were single-center, with 50% (8 of 16) undertaken in Europe, 17,22,26,[36][37][38][39][40] 44% (7 of 16) in North America, 24,25,27,[41][42][43][44] and one in Australia. 45 Study inclusion periods ranged from 3.5 to 16 years, 25,26 with average ages from 2 to 13 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study was translated from French 36 ; others were in English. All but two studies 17,36 were single-center, with 50% (8 of 16) undertaken in Europe, 17,22,26,[36][37][38][39][40] 44% (7 of 16) in North America, 24,25,27,[41][42][43][44] and one in Australia. 45 Study inclusion periods ranged from 3.5 to 16 years, 25,26 with average ages from 2 to 13 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…No studies were randomized, 69% (11 of 16) were case series following one group only (seven were retrospective, 25,27,38,40,[43][44][45] whereas four did not state whether they were retrospective or prospective 26,37,41,42 ), and 31% (5 of 16) were cohort studies 17,22,24,36,39 comparing two groups (only one was prospective 39 ). Comparator groups included children with gastrostomies for noncancer/non-BMT reasons (typically neurological impairment 17,24,39 ) or NGT during cancer treatment without 17 or with BMT.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Reported complication rates associated with GT insertion in children with cancer are high (60%–90%) compared with rates reported in adults with cancer (predominantly head and neck cancer) . Reports of complication rates of GT insertion in children with cancer compared with other children (predominantly with neurological impairment) are conflicting.…”
Section: Complicationsmentioning
confidence: 99%
“…Data specific to children with cancer are limited and must be interpreted with caution. One retrospective study showed a higher rate of postoperative complications in PEG tubes ( n = 28) compared with openly placed GT ( n = 84) in children with cancer . Another retrospective study reported a significantly higher infection rate in GT placed by open surgical technique compared with those placed endoscopically or laparoscopically …”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation